Demonstrasi Plot Padi IPB 3S dan IPB 9G sebagai Upaya Peningkatan Pengetahuan Petani Desa Mekarharja, Kecamatan Purwaharja, Kota Banjar - Tika Anisa Padar Wati; Hajrial Aswidinnoor; Memen Surahman; Danang Aria Nugroho (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
Demostration rice plot of IPB 3S and IPB 9G varieties were at Mekarharja village, Purwaharja district, Banjar city. The demostration plot area of one hectare is spread over three hamlets including Randegan, Cibentang, and Pasirleutik hamlets. Stasiun Lapang Agro Kreatif (SLAK) program aims to develop IPB 3S and IPB 9G varieties of rice in an effort to increase farmer resources and rice production. Application of IPB 3S dan IPB 9G rice cultivation technology through training and field assistance to farmers. Farmers are given training and assistance to utilize cow dung and rice straw, seed treatment and tillage technology, and balanced fertilization technology. There are farmers’ knowledge increases about the use of cow dung and rice straw to increase rice production, and balanced seed treatment and fertilization. Farmers can apply cultivation technology easily because the materials used are easy to obtain and simple technology implementation procedures. The application of rice cultivation technology that has been carried out by most farmers in the village of Mekarharja. Farmers’ knowledge increases about the management of agricultural and livestock waste which can be used as organic fertilizer. The submitted science and technology was accepted and applied well by the farmers.